Accessibility and emotionality of online assessment feedback: Using emoticons to enhance student perceptions of marker competence and warmth. (January 2020) - Moffitt, Robyn L.; Padgett, Christine; Grieve, Rachel
Abstract: Assessment feedback is one of the most powerful learning tools, and in higher education this feedback is increasingly being provided online. The current study investigated the inclusion of emoticons as a method through which to enhance student perceptions of the accessibility and emotionality of written online assessment feedback. Undergraduate students ( N = 241) were presented with an online faux essay along with associated written feedback typical of the comments students would receive in the higher education context. The feedback was identical except for the inclusion of emoticons. Using a between-groups design, emoticons were manipulated in two ways: frequency (none, 1, 3, or 6) and valence (happy, sad, or confused). The use of happy emoticons produced significantly higher perceptions of marker warmth when compared to no emoticons, or when negatively valenced emoticons were included. Furthermore, marker competence was significantly higher when 3 happy face emoticons were presented in the feedback than when 3 sad or confused faces were included. Student perceptions of feedback quality and marker professionalism were not affected by emoticon use. Thus, the results suggest that instructors can use positively valenced emoticons to inject some fun, warmth, and emotionality in written online assessment feedback without sacrificing feedback quality or professional integrity. Highlights: Experimentally manipulated emoticon valence and frequency in assessment feedback. Including happy emoticons in feedback increased perceptions of marker warmth. Marker competence was rated higher with happy than sad or confused face emoticons. Feedback quality and marker professionalism were unaffected by emoticon inclusion. Happy face emoticons convey emotionality without compromising feedback quality.